School / Madrasah Program Development Plan: Literature Review - Yarnita, Yetti; Wendra, Zetria; Sari, Sri Deska; Asmendry, Asmendry; Sari, Milya (JUPE : Jurnal Pendidikan Mandala, 2024)
School/madrasah program development plans are an important strategic step in improving the quality of education. This article discusses various components that support the planning process, starting from environmental analysis, preparing a vision and mission, to implementing and evaluating programs. The use of planning models, such as SWOT and ADDIE, helps identify the strengths, weaknesses, opportunities and threats facing the school. Continuous evaluation and stakeholder involvement are also emphasized as key elements in ensuring program success. Challenges in development, such as resistance to change and limited resources, are overcome through appropriate strategies. The final results of the development of this program are expected to make a significant contribution in improving the quality of education and school readiness in facing the era of globalization and technological progress.